Dark carrier dynamics and electrical characteristics of organic solar cells integrated with Ag-SiO2 core-shell nanoparticles - Chan, K.; Elumalai, Naveen Kumar; Tayebjee, M.; Uddin, A.; Pillai, S. (ELSEVIER SCIENCE SA, PO BOX 564, 1001 LAUSANNE, SWITZERLAND, 2017)
Short circuit current increase in organic solar cells due to increased light absorption, mediated by metal nanoparticles is widely reported, but the underlying influence of changes in electrical properties of dark carriers and trap states in organic solar cells is not well explored. In this work, Ag-SiO2 core-shell nanoparticles in an optimized blend with ZnO sol-gel was used to improve device performance of PCPDTBT:PC70BM based organic solar cells and allowed direct examination of the electrical properties while isolating optical effects. Impedance spectroscopy revealed dopant-induced dark carriers from impurities in the active layer or surface trap states. The modified ZnO devices containing dopant-induced dark carriers exhibited enhanced carrier mobility and reduced lifetime compared to reference devices. We attribute the reduced dark carrier lifetime to short-lived and shallow trap states that reduce monomolecular recombination under illuminated operating conditions, thereby improving charge extraction efficiency. A combination of changes in dark carrier dynamics and improvements in electrical properties was responsible for the improved fill factor and efficiency of devices with Ag-SiO2 core-shell nanoparticles.